Extracontractual referrals: safety valve or administrative paperchase? - Ghodse, B. (BMJ Group, 1995)
OBJECTIVE--To describe the extracontractual referrals of residents of a health authority during a six month period in 1994, identifying the number and cost of emergency and non-emergency referrals, including the number of cases costing more than 20,000 pounds and those cases when payment was refused. DESIGN--Descriptive analysis of all extracontractual referrals submitted to the health authority between 1 April and 30 September 1994. SETTING--A health authority covering a population of 614,000. RESULTS--Payment of 2,583,693 pounds was made to 263 different providers for 2400 episodes of care, of which 1469 were emergencies and 931 were elective or tertiary referrals. Authorisation was granted for an additional 1376 referrals for future treatment but was refused in 713 instances, mostly for technical reasons. Sixteen extracontractual referrals together accounted for over a fifth of total expenditure during the study period. CONCLUSIONS--Handling large numbers of episodes of care on an individual cost per case basis imposes an enormous administrative burden on both purchasers and providers, diverting money away from patient care. Extracontractual referrals also expose health authorities to considerable financial risk and may undermine commissioning strategies. Measures are proposed to limit the number of episodes handled in this way.